Features of automatic working time control systems - Cherednichenko, T.; Sotnik, S. (ХНУРЕ, 2025)
The research is devoted to the development and implementation of automatic working time control systems, which are an important tool for improving personnel management efficiency and optimizing business processes. The paper discusses the features of creating a web application based on the Vuetify framework, using the SQLite database and the server part on Node.js. The main focus is on automating work time accounting processes, including employee check-in/check-out registration, performance analysis, and report generation. The study analyzes the advantages of using a lightweight SQLite database for small and medium-sized organizations, as well as the integration of modern front-end technologies to create a user-friendly interface. The work includes the practical implementation of the system, demonstrating its functionality, and provides an analysis of the challenges associated with ensuring data security, scalability, and integration with other systems. Visual elements such as diagrams and graphs contribute to a better understanding of the structure and functionality of the developed application. The study emphasizes the importance of automated systems for modern organizations, offering recommendations for their implementation and improvement. Дослідження присвячене розробці та впровадженню автоматизованих систем контролю робочого часу, які є важливим інструментом для підвищення ефективності управління персоналом та оптимізації бізнес-процесів. У статті обговорюються особливості створення веб-додатку на базі фреймворку Vuetify, з використанням бази даних SQLite та серверної частини на Node.js. Основна увага приділяється автоматизації процесів обліку робочого часу, включаючи реєстрацію приходу/виходу працівників, аналіз продуктивності та формування звітів. Дослідження аналізує переваги використання легкої бази даних SQLite для малих та середніх організацій, а також інтеграцію сучасних фронтенд-технологій для створення зручного інтерфейсу. Робота включає практичну реалізацію системи, демонструючи її функціональні можливості, а також надає аналіз проблем, пов'язаних із забезпеченням безпеки даних, масштабованістю та інтеграцією з іншими системами. Візуальні елементи, такі як діаграми та графіки, сприяють кращому розумінню структури та функціональності розробленого додатку. Дослідження підкреслює важливість автоматизованих систем для сучасних організацій, надаючи рекомендації щодо їх впровадження та вдосконалення.
Keywords: time and attendance systems; управління персоналом; web application; human resources management; системи обліку часу та відвідуваності